The Peace journalism as a builder democratic. - Romero Ortega, Aldo Benito; Peñafiel Arcos, Edison Boanerges (SATHIRI, 2019)
The current socio-political panorama in Latin America has highlighted the valid character and importance of peace journalism as a positive catalyst in violence scenes through the generation and diffusion of informative contents that allow citizens to link to the social construction of its reality from an objective and democratic approach. However, this model has come into direct confrontation with the actual paradigms, since they demand that all media and mass media are aligned according to the interests of the hegemonic groups -with this respective inevitable consequences- and this logic has had a negative impact in the way of acting of this type of journalism.
Keywords: peace journalism; conflict; democracy; comunication